2018
DOI: 10.1371/journal.pone.0199636
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of diffusion-weighted imaging for prostate cancer: Peripheral zone versus transition zone

Abstract: ObjectivesDiffusion-weighted imaging (DWI) has been shown to be an important component of multiparametric magnetic resonance imaging (mpMRI). We compared performance of DWI for detection of prostate cancer (PCa) in peripheral zone (PZ) and transition zone (TZ) of prostate.Materials and methodsWe reviewed data of 460 subjects who underwent preoperative 3.0-Tesla mpMRI and subsequently radical prostatectomy. Level of suspicion for PCa was graded using 5-grade Likert-scale from DWI. Topographic analyses were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Lexicon terms indicating a restricted diffusion in PZ lesions showed favorable combinations of both relatively high PPVs and high NPVs (e.g., PPV of 50.7% and NPV of 90.5% for the term "restricted diffusion"). Our work therefore confirms the importance of diffusion-related findings in the PZ [21][22][23]. [3].…”
Section: Discussionsupporting
confidence: 88%
“…Lexicon terms indicating a restricted diffusion in PZ lesions showed favorable combinations of both relatively high PPVs and high NPVs (e.g., PPV of 50.7% and NPV of 90.5% for the term "restricted diffusion"). Our work therefore confirms the importance of diffusion-related findings in the PZ [21][22][23]. [3].…”
Section: Discussionsupporting
confidence: 88%
“…As this study was initiated in 2015, at that time we used cognitive targeting at our institution. Although it seems intuitive that cognitive targeting should be less accurate than MRI-ultrasound fusion or in-gantry biopsy techniques (32), recent studies from Monda et al and Lee et al indicate that there is still a lack of consensus regarding the superiority of ultrasound-MR fusion over cognitive targeting (33,34). Future work can explore additional forms of targeting.…”
Section: Discussionmentioning
confidence: 99%
“…Because of technique and scanner dependence, reproducibility across institutions and different MRI platforms is limited. Diagnostic performance is consistently lower in the transition zone relative to the peripheral zone [20]. In initial pilot studies, RSI has been shown to be a promising independent biomarker; however, these studies have been limited by small sample size and selection bias, applied only to surgical populations that underwent radical prostatectomy [810].…”
Section: Discussionmentioning
confidence: 99%